Evaluation of Emissions by Different Analysis Method at Hot Mix Asphalt Plant Combustion Source - Hafdaoui, Hichem; Abdul Rahman, Farahiyah; Hashim, Nur Anira Asyikin; Nashruddin, Thanwa Filza (International Journal of Integrated Engineering, 2022)
The combustion process for the asphalt mixing in hot mix asphalt (HMA) plant can produce harmful flue gases emission into the atmosphere. Combustion activities produce heat for industrial usage when fuel reacts with oxygen in the air under suitable conditions. High concentrations of undesirable emissions can be formed if the combustion is not properly controlled during the reaction. This paper gives an overview on the method and measurement of these emissions in combustion analysis by focusing on the three types of analysis methods which are laboratory testing analysis, on-site emission analysis, and theoretical analysis. Three types of data were prepared in order to achieve the objective of the study, which are literature study, site visit, and laboratory analysis. The result shows that there is slightly different emission results even though they came from the same source. Clearly, the analysis shows that the air-fuel ratio during combustion can have a significant effect on the emission result. The excess air supplied can cause dilution to the emission and leads to a low emission value.